ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEMBUHAN PASIEN PENYAKIT FLU BURUNG - Wilandari, Yuciana; Safitri, Diah (MEDIA STATISTIKA, 2009)
Avian influenza is contagion which caused by influenza virus type H5N1 often cause death. Avian influenza anticipated to be influenced by gender, age, epidemiology and case, to know the factors have a significant effect used by independent test. is later on made model of regresi binary logistics. Then obtained by factor having an effect is case and epidemiology, that is made regression logistics model. Someone which including case of suspect to be able to have probability recover bigger than someone which including confirmation case, someone which contact with dead an avian to be able to have probabilityÂ  recover smaller than someone which no contact.